2018
DOI: 10.1016/j.bbi.2018.09.017
|View full text |Cite
|
Sign up to set email alerts
|

Myelination induction by a histamine H3 receptor antagonist in a mouse model of preterm white matter injury

Abstract: Fifteen million babies are born preterm every year and a significant number suffer from permanent neurological injuries linked to white matter injury (WMI). A chief cause of preterm birth itself and predictor of the severity of WMI is exposure to maternal-fetal infection-inflammation such as chorioamnionitis. There are no neurotherapeutics for this WMI. To affect this healthcare need, the repurposing of drugs with efficacy in other white matter injury models is an attractive strategy. As such, we tested the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 64 publications
1
15
0
1
Order By: Relevance
“…The utility of the mice with IL-1β-induced inflammation and subsequent diffusion white matter injury used here is that the injury is broadly comparable in nature to that seen in our patient samples. Specifically, this model displays the hallmarks of injury observed in contemporary preterm born infants: hypomyelination, axonopathy, oligodendrocyte dysmaturation and also, reported here and previously, no gross cortical injury evidenced by no change in cortical neuronal number (Favrais et al, 2011; Schang et al, 2014; Krishnan et al, 2017; Rangon et al, 2018). In this model, females have a less severe and more transient phenotype, which is why they were not used in this study (unpublished data), suggesting a bias seen in the animal model similar to that observed in the human population (Marlow et al, 2005).…”
Section: Discussionsupporting
confidence: 72%
“…The utility of the mice with IL-1β-induced inflammation and subsequent diffusion white matter injury used here is that the injury is broadly comparable in nature to that seen in our patient samples. Specifically, this model displays the hallmarks of injury observed in contemporary preterm born infants: hypomyelination, axonopathy, oligodendrocyte dysmaturation and also, reported here and previously, no gross cortical injury evidenced by no change in cortical neuronal number (Favrais et al, 2011; Schang et al, 2014; Krishnan et al, 2017; Rangon et al, 2018). In this model, females have a less severe and more transient phenotype, which is why they were not used in this study (unpublished data), suggesting a bias seen in the animal model similar to that observed in the human population (Marlow et al, 2005).…”
Section: Discussionsupporting
confidence: 72%
“…To validate the in vivo neurotherapeutic efficacy of our novel nanocarrier-mediated WNT agonist therapy, we assessed the IL-1β-induced myelination deficit by measuring Mbp mRNA at P10, MBP protein via western blotting at P15 and axonal myelination via electron microscopy at P30. We have previously shown in this model that there is an accumulation of immature oligodendrocytes (NG2+ and PDGFRa+), reduced small calibre axonal myelination and reduced expression of myelin proteins (Favrais et al, 2011;Schang et al, 2014;Rangon et al, 2018).Treatment with i.p. 3DNA L803mts Cy3 significantly prevented the IL-1β-induced reduction in Mbp mRNA ( Figure 7B) and alleviated the IL-1β-induced reduction in MBP proteins ( Figure 7C,D, Supp Figure 7A).…”
Section: A Wnt Pathway Agonist Delivered Specifically To Mg By a Nanomentioning
confidence: 92%
“…In addition to timing, also inclusion of an inflammatory component is thought to be key to the development of translational animal models of EoP. In recent years, rodent models of EoP have been developed (Zeng et al, 2018), including several multiple hit models that combined fetal inflammation with post-natal hypoxia (van Tilborg et al, 2018a) or multiple post-natal injections of cytokines (Rangon et al, 2018). Also larger animal models of EoP have been developed, mostly using preterm lambs (Li et al, 2016; Wassink et al, 2017; Gussenhoven et al, 2018), piglets (Andersen et al, 2016; Buddington et al, 2018), and baboons (Griffith et al, 2012).…”
Section: Discussionmentioning
confidence: 99%